Influence of breakfast and meal frequency in calcium intake among pregnant adolescents - Maira Pinho‐Pompeu; Daiane Sofia Morais Paulino; Fernanda Garanhani Surita (Wiley, 2020)
Abstract Calcium is an essential micronutrient that plays a role in growing and pregnancy, and its necessity is increased during pregnancy in adolescence. Thus, the aim of the study is to describe the daily calcium intake and its associations with dietetic habits, sociodemographic data and perinatal outcomes among pregnant adolescents. A prospective cohort study was conducted among primiparous adolescents who started prenatal care before 20 weeks of gestation. Sociodemographic data, weight and height, 24‐h dietary recall (24hRec) and perinatal outcomes were collected over four meetings (three during pregnancy and one in puerperium). All 24hRecs were analysed by the Nutrition Data System for Research (NDSR)® programme, and descriptive analysis and univariate and multivariate logistic regression were done. A total of 150 pregnant adolescents were included, with a mean of daily calcium intake of 659.9 mg (50% of recommended intake). Adolescents who ate more than three meals per day (89.3%), and ate breakfast every day (69.3%), were shown to have higher daily calcium intake, odds ratio (OR CI 95%) of 3.4 (1.0, 11.0) and 16.8 (1.0, 302.1), respectively. No correlation was observed between calcium daily intake and sociodemographic data or perinatal outcomes. Dairy products were the foods that mostly contributed to achieving recommended daily calcium intake. In our cohort, pregnant adolescents had a low daily calcium intake. They should be advised to eat more than three meals per day, eat breakfast in particular, increase the consumption of calcium rich‐foods, such as dairy products and green leafy vegetables, and consider calcium supplementation.